My school's a zoo. - Smith, Stu (New York : Scholastic, 2004)
A young boy, with a wild imagination, goes on a fantasy-filled trip to the zoo.
K-3
Keywords: Fantasy - Fiction; Zoo Animals - Fiction; Jungle Animals - Fiction; Catrow, David illus; Stories in Rhyme